Flea-borne Bartonella grahamii and Bartonella taylorii in Bank Voles - Kevin J. Bown; Malcolm Bennett; Michael Begon (Emerging Infectious Diseases, 2004)
Bartonella species are increasingly associated with a range of human and animal diseases. Despite this, we have a poor understanding of the ecology and epidemiology of many species, especially those circulating in wild populations. Previous studies have demonstrated that a diverse range of Bartonella species are abundant in wild rodent populations; little is known regarding their modes of transmission, although both direct and indirect routes have been suggested. In this study, with bank voles (Clethrionomys glareolus) as the host species, we demonstrate that the rodent flea Ctenophthalmus nobilis is a competent vector of at least two Bartonella species, B. grahamii, which has previously been associated with human infection, and B. taylorii. In contrast, no evidence of either horizontal or vertical transmission was seen in bank voles inoculated with B. taylorii maintained in an arthropod-free environment; this finding suggests that fleas may be essential for transmitting some Bartonella species.